Targeting Fatigue in Stroke Patients. (30th November 2011) - Barritt, Andrew W.; Smithard, David G.
Abstract : Symptoms of fatigue are often reported by patients in both the acute and chronic stages of recovery following a stroke. It is commonly associated with low mood and sleep disturbances, but can arise in their absence. However, it has also been associated with poorer long-term outcome and, as such, its aetiology warrants a greater understanding. There is convincing evidence that inflammatory cascades and cytokine signalling precipitated by the infarct promote fatigue, and these pathways may harbour therapeutic targets in its management.